Traffic Impact Analysis of the XYZ Livin Cluster Development at Tanjung Bunga, Makassar City - Indah Nur Afiah; Nursafanah Dzakiyah Almakassari (Universitas Sulawesi Barat, 2025)
The development of Cluster XYZ Livin in the Tanjung Bunga area of Makassar has the potential to impact surrounding traffic conditions. This study analyzes the traffic impact of the development using a quantitative, field survey-based method. Traffic volume, free-flow speed, and road capacity values were processed from data collected on weekdays and weekends. The Level of Service (LOS) analysis refers to the Indonesian Highway Capacity Manual (MKJI 1997), using the volume-to-capacity ratio (V/C) for road segments and Degree of Saturation (DS) for intersections. For road segments, results show that although vehicle volume increases during peak hours, most V/C values remain within categories A–B across various scenarios, including existing conditions, construction phase, operation in 2025, and projections for 2030. The lowest LOS at intersections occurred during weekday evening peak hours, classified as category C. The existing road capacity is still sufficient to accommodate additional traffic load. Recommended mitigation measures include traffic management and road widening. This study serves as a reference for planning and mitigating traffic impacts to ensure development does not disrupt transportation performance.